Development of a BR–UASB–DHS system for natural rubber processing wastewater treatment. Issue 4 (16th February 2016) - Watari, Takahiro; Thanh, Nguyen Thi; Tsuruoka, Natsumi; Tanikawa, Daisuke; Kuroda, Kyohei; Huong, Nguyen Lan; Tan, Nguyen Minh; Hai, Huynh Trung; Hatamoto, Masashi; Syutsubo, Kazuaki; Fukuda, Masao; Yamaguchi, Takashi
Abstract : Natural rubber processing wastewater contains high concentrations of organic compounds, nitrogen, and other contaminants. In this study, a treatment system composed of a baffled reactor (BR), an upflow anaerobic sludge blanket (UASB) reactor, and a downflow hanging sponge (DHS) reactor was used to treat natural rubber processing wastewater in Vietnam. The BR showed good total suspended solids (TSS) removal of 47.6%, as well as acidification of wastewater. The UASB reactor achieved a high chemical oxygen demand (COD) removal efficiency of 92.7 ± 2.3% and energy recovery in the form of methane with an organic loading rate of 12.2 ± 6.6 kg-COD m −3  day −1 . The DHS reactor showed high performance in residual organic matter removal from UASB effluent. In total, the system achieved high-level total COD removal of 98.6% ± 1.2% and TSS removal of 98.0% ± 1.4%. Massive parallel 16S rRNA gene sequencing of the retained sludge in the UASB reactor showed the predominant microbial phyla to be Bacteroidetes, Firmicutes, Proteobacteria, WWE1, and Euryarchaeota . Uncultured bacteria belonging to the phylum Bacteroidetes and Phylum WWE1 were predominant in the UASB reactor. This microbial assemblage utilizes the organic compounds contained in natural rubber processing wastewater. In addition, the methane-producing archaea Methanosaeta sp. and Methanolinea sp. were detected.